The effects of MRI personnel shortages on waiting time and Bed Stay Costs in a Tertiary Referral - Sithole, Nhlanhla (My University, 2019)
The study evaluates the effects of the removal of overtime payment on MRI scan personnel on waiting time and bed-stay cost resulting from decreased MRI scanning hours, which occurred as a result of MRI personnel over-time pay withdrawal dated 20th April 2012, as a surrogate representation of the benefit of increasing scanning hours. The study motives are to determine the number of patients occupying hospital beds while awaiting MRI scans over a 6-month period in a tertiary referral radiology department, BEFORE and AFTER the 20th April 2012, when overtime payment for technologists was terminated, to determine number of ‘waiting days’ (waiting time), overall, and per patient, and bed stay cost for those patients identified in objective one BEFORE and AFTER the specific event above, where overtime payment was terminated. The researcher identified a target population of 300 MRI scanning patients registered at Charlotte Maxeke Johannesburg Academic Hospital MRI radiology department, during the period under study and employed a simple random sampling technique to choose the research sample frame. Different diagnostic tests were conducted in order to find whether the data collected was best fit or not for the research in question. These tests formed part of a data clean-up exercise. Tests conducted enabled the researcher to have objective and reliable research results. The data adequacy requirement tests include measures of central tendency, Pearson product moment correlation coefficient, coefficient of determination, autocorrelation, chi-square, stationarity, long-term relationship and Granger causality. The researcher found out that the impact of the removal of overtime on MRI scan personnel resulted in longer waiting times by patients and a corresponding higher bed stay costs at Charlotte Maxeke referral hospital over the period under the study. The research results further indicate the removal of overtime payment had a Granger effect on MRI scan patients’ waiting time, which ultimately led to high bed stay costs. The researcher recommends that referral hospitals, in conjunction with the Ministry of Health, must ensure that MRI scan personnel are well trained and equipped to deliver quality health services. The MRI scan personnel must periodically be sent for retraining through medical workshops, seminars and refresher courses to ensure that the MRI scan personnel are up to date with the current trends in the medical fraternity.
A thesis submitted in fulfilment of the requirement for the degree Masters in Medicine in Diagnostic Radiology at Wits Medical School to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2019
Keywords: Diagnostic Imaging; Magnetic Resonance Imaging; Cancer--Imaging